Used Lubricating Oil Treatment and Reuse for Sustainable Production Processes in Cement Industry - Lestianingrum, Erna; Marbelia, Lisendra (Eksergi, 2025)
Used lubricating oil is one type of hazardous waste produced in the chemical industry, including the cement industry. PT. ITP Unit Palimanan has obtained a permit to process hazardous waste in the form of used lubricant oil since February 21, 2023. Therefore, starting from March 2023, PT. ITP Unit Palimanan has been utilizing used lubricant oil for open chain lubrication. The used lubricant oil, which is dark in color and contains a high amount of particles, is reprocessed through a filtration process before being used. In this process, the contaminating particles are reduced, and the used lubricant oil can be reused as lubrication material for open chains within PT. ITP Unit Palimanan itself. In 2019-2021, the average total generation of used lubricant oil was around 125 tons per year. Of this amount, approximately 90% was suitable for reuse as it contained metal and water levels below the threshold limits. Through this reuse process, the substitution of lubricant oil for open chain equipment can be reduced by 95.5%, equivalent to Rp 1,514,556,289 per year or Rp 4,207,101 per day. Besides the cost savings, PT. ITP Unit Palimanan can significantly reduce the burden of used lubricant oil waste on the environment through this innovation.